Financial Inclusion : Can it Meet Multiple Macroeconomic Goals? - Sahay, Ratna (Staff Discussion Notes; Staff Discussion Notes ;, 2015)
Using several recently available global datasets, this Staff Discussion Note examines macroeconomic effects of financial inclusion. It finds significant benefits to economic growth from financial inclusion, but the benefits diminish as financial inclusion and depth become large. Broadening access to credit can compromise economic and bank stability in countries with weak bank supervision. Other forms of financial inclusion-such as access to and use of bank accounts, branches, and ATMs-do not hurt stability, and can be promoted extensively. The note finds that gaps in financial inclusion are associated with economic inequality, but the association appears relatively weak.